Postmigrant club cultures in Urban Europe. - (:unkn) unknown (Lang, 2015)
How do young people with migration backgrounds take part in and shape urban leisure socialities in European cities? Presenting results of a long-term ethnographic research project carried out in ethnic club scenes in Paris, London and Berlin, this book challenges assumptions about migrant community dynamics and ethnic segregation. Examining both heteronormative and "queer" scenes, the contributors to this volume give insights into how clubbing socialities are related to the wider life contexts of different postmigrant groups and the challenges they face in metropolitan centres. Far from simply celebrating ethnic community, British Asian, German Turkish and French Caribbean club scenes respond to intersecting dynamics of racism, gentrification, sexism, homophobia and class stratification.
Keywords: Freizeit; Integration; Jugendlicher; Segregation; Stadtforschung; Migrant; Club; Jugendlicher; Junger Erwachsener; Jugendkultur; Subkultur; Ethnische Minderheit; Metropole; Nachtleben; Soziales Netzwerk; Migrationshintergrund; Homosexualität; Diskriminierung